Unlearning/Relearning in Processesof Business Information Systems Innovation - Pighin, Maurizio; Marzona, Anna (Journal of Information and Organizational Sciences, 2011)
Unlearning is defined as throwing away concepts learnt in the past to give space for possible new learning. The learning process that supports deep change should be composed by different unlearning-learning phases, both at the individual level and at a more general organizational level. Must unlearning and relearning concepts be explicitly considered in business process reengineering based on the reorganization of information systems? This paper tries to answer this question, by describing the impact of change in information systems on the knowledge model of an organization. The analysis of a recent case study of information systems innovation, permit us to highlight common deficiencies in the design of information systems reengineering processes, particularly in SME. The paper ends with the suggestion of “good practices” that could permit the success of innovation processes by reducing the risk of failure due to excessive resistance to change.